Strategic Forecasting: AI-Powered Techniques - KVS, Rishikesh Biswas (Journal of Global Economy, Business and Finance, 2025)
To understand how artificial intelligence can improve business intelligence, this research paper aims to establish how the two concepts can be combined for better BI strategic forecasting. Thus, the findings of this study, which covers the analysis of numerous AI- driven BI methods and their use across different industries, can help understand the potential of such tools to enhance decision-making and outcomes for organizations. Primary data is gathered from reports, periodicals, and case studies, while secondary data involves statistical analysis of technologies' influence. The present research results reveal that organizations handling artificial intelligence in BI show a marked increase in accuracy and efficiency and reduced costs. However, critical issues like data quality, implementation costs, and lack of adequate skills must be overcome for the plan to work.